The effect of bleaching agents on human enamel microhardness - Savić-Stanković Tatjana; Karadžić Branislav (Serbian Medical Society - Dental Section, Belgrade, 2010)
Introduction. Bleaching agents can cause alteration of hard tissues of the tooth. The aim of this study was to evaluate the effect of two different concentrations of carbamide peroxide (10% and 35%) on human enamel microhardness. Material and Methods. The study was conducted on ten extracted teeth divided into two groups. The teeth were sectioned in mesiodistal direction using the diamond disc in order to obtain experimental and control samples. First group was exposed to the concentration of 10% carbamide peroxide (Opalescence gel, Ultradent. Pro, US) at the time intervals that corresponded to home night bleaching technique of vital teeth. Second group was exposed to high concentration of 35% carbamide peroxide (Opalescence Quick, Ultradent. Pro, US) at the time intervals that corresponded to the professional bleaching technique of vital teeth. Control samples were exposed to artificial saliva for the same time intervals as the samples from experimental group. Knoop's test for enamel microhardness was performed at the beginning, after the first phase of therapy, after the therapy was completed and after three weeks of exposure to artificial saliva. The results were statistically analyzed using analysis of variance (ANOVA) and Student t-test. Results. The microhardness values of enamel samples treated with 10% carbamide peroxide decreased after 8 hours (261 khn) and three weeks of treatment (222 khn) but increased after three weeks of exposure to artificial saliva (263 khn). The decrease of enamel microhardness of the samples treated with 10% carbamide peroxide was not statistically significant. The microhardness values of enamel samples treated with 35% carbamide peroxide were reduced after 1 hour (235 khn) and 3 hours (190 khn) and increased after three weeks of exposure to artificial saliva (241 khn). Microhardness of enamel treated with 35% carbamide peroxide was significantly decreased in experimental samples compared to controls. Conclusion. Carbamide peroxide in concentration of 35% leads to the significant decrease in enamel microhardness compared to 10% carbamide peroxide.